DEMOKRASI DALAM PERSPEKTIF TABLOID MEDIA UMAT DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR MATA KULIAH ANALISIS WACANA KRITIS DI PERGURUAN TINGGI - Suryana, Agus (2015)
This research entitled "Democracy in Media Umat Tabloid Perspective and That Utilization as A learning Sources at Critical Discourse Analysis Subject in Higher Education". The background of this research is motivated by the incessant media of the discourse of democracy which have long been topics of discussion and study center in society. The term democracy nowadays cannot be removed from any political discourse, in the context of support, half supporting, or opposing. Through word and sentence as a messenger and purposeful, the media makes the discourse of democracy as a political system that is complete entity and almost without criticism. It certainly can be used as a propaganda tools to the public media which has low political awareness, so unbalanced presentation of the news will make all the unpopular policies from the on behalf of democracy is not responded with alacrity and critically, they eventually became the attenuated and victimization. The purpose of this study is to investigate the use of words and phrases used in spreading democracy by Media Umat. In addition, to find a description of democracy in Media Umat's news and designing teaching materials for critical discourse analysis of democracy. The theoretical benefits of this research is to develop knowledge and enhancer treasures field of discourse analysis. The practical benefits for faculty and students who take critical discourse analysis subject is to develop a critical attitude, especially in the discourses against mainstream ideas like democracy. This research method is descriptive with critical discourse analysis approach. The analysis is about the implementation of democracy-themed news content that published in Media Umat. Then, the data will be analyzed using discourse analysis model introduced Roger Fowler, et al., the data collected in the form of descriptive data about the choice of vocabulary and grammar. The data were collected, selected and analyzed descriptively. The data then presented, described, and interpreted until a conclusion can be drawn. Based on the context of the implementation and results of the analysis on the news discourse of democracy by Media Umat, can be affirmed that based on the results of the analysis of news discourse of democracy in the Media Umat tabloid, who want to build discourse is positioned democracy as a system of paradoxes and discourse process through the use of a certain vocabulary and grammar. The results of the analysis and discussion of this study can support teaching materials used as subjects of critical discourse analysis in the form of learning modules. Pemanfaatannya Sebagai Bahan Ajar Mata Kuliah Analisis Wacana Kritis di Perguruan Tinggi". Kajian yang dilakukan pada tesis ini adalah untuk mengetahui penggunaan kata, kalimat, dan gambaran demokrasi dalam pemberitaan di tabloid Media Umat, serta untuk mengetahui ideologi Media Umat dalam pemberitaan demokrasi tersebut, sekaligus merancang bahan ajar analisis wacana kritis tentang demokrasi. Secara keseluruhan tesis ini terbagi atas enam bab. Bab I merupakan pendahuluan yang berisikan latar belakang penelitian, identifikasi masalah, rumusan masalah, tujuan penelitian, dan manfaat penelitian. Bab II merupakan kajian teoretis yang merupakan gambaran singkat perihal demokrasi, analisis wacana kritis dalam teks media, perihal tabloid Media Umat, penelitian yang relevan, perihal bahan ajar dan modul. Bab III merupakan uraian mengenai metodologi penelitian yang memuat metode penelitian, metode pengumpulan data, fokus penelitian, metode analisis data, interpretasi data, korpus data, dan definisi operasional. Bab IV berisikan temuan penelitian dan pembahasan, analisis dan hubungan teori dengan temuan-temuan penelitian lain yang relevan. Bab V adalah pemanfaatan wacana demokrasi sebagai bahan ajar berupa modul dan Bab VI adalah simpulan dan saran penelitian. Tesis ini masih menyisakan peluang perbaikan dalam berbagai hal. Oleh karena itu adanya saran dan kritik dari semua pihak sangat diharapkan untuk membantu penyempurnaan penulisan karya tulis berikutnya. Semoga tesis ini dapat bermakna dan memberikan manfaat bagi kehidupan. Amin.